Pengaruh Penerapan Media Flashcard untuk Meningkatkan Kemampuan Membaca Permulaan pada Kelompok B Di TK Dharmawanita Persatuan Sukorejo - Risky Mila Sary (Journal of Islamic Education for Early Childhood, 2022)
The main problem in this study is whether there is an effect of applying flashcard media to improve the early reading ability of group B in TK Dharma Wanita Persatuan Sukorejo Sidayu Gresik. This study uses a quantitative approach to the type of experiment. The design used in this study is the Pretest-Posttest One Group Design. In this study, the sample used was 28 children, so this study used non-parametric statistics. The data shows that the average value in the pretest and posttest 155 increased to 256 when the treatment was given. The results of the analysis of the statistical test output above, Tcount > Ttable, i.e. 4.663 > 2.048. So it can be concluded that Ha is accepted to support the hypothesis formulated earlier, with the acceptance of the hypothesis which shows that there is an effect on the application of flashcard media to improve the early reading ability of group B in TK Dharma Wanita Persatuan Sukorejo Sidayu Gresik.